Handling Teacher Spiritualism Based On Local Wisdom Towards Organizational Citizenship Behavior (OCB) - Feriska Listrianti; Fathor Rozi; Adi Nur Cahyono (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2023)
This study aims to analyze the Handling of Teacher Spiritualism Based on Local Wisdom towards Organizational Citizenship Behavior (OCB). This research was conducted at the Madrasah Ibtidhaiyah Tarbiyatul Hasan Sumberasih Probolinggo institution using qualitative methods of case study types. The sources of informants in the study were the principal and the teacher council. Data collection techniques using observation, in-depth interviews and documentation. While the data analysis uses data display, data reduction and drawing conclusions. The results of this study show that in handling spiritualism teachers are first, education and the cultivation of spiritual values of teachers. Second Handling Teacher Spiritualism Based on Local Wisdom Against Organizational Citizenship Behavior (OCB), Strategies The work ethic of teacher spiritualism. Third, teacher spiritualism education based on local wisdom and fourth, Media Organizational Citizenship Behaviour in achieving targets.